The methodological competence of the teacher of foreign languages from a configurational approach - ALBERTO ROMÁN MEDINA BETANCOURT (Universidad del Magdalena, 2013)
This article shows a proposal of the definition of what is meant by methodological competence for foreign language teaching from a configurational perspective. A definition is given to the term competence and from this definition, the content of methodological competence was determined through the subcompetences that foreign language teachers should have in order to be considered competent from the methodological stand point. The results which are presented in the article might be considered very useful, both from the theoretical and from the practical points of view. They can be used as a guide for the preparation of teachers with the aim of obtaining higher levels of efficiency in the formation and development of the verbal skills in foreign languages in his students. Such a goal is of great importance nowadays all over the world.